Board characteristics, investors’ confidence and firm value : Malaysian evidence - Lim, Ann Ley; Fathyah Hashim,; Zaini Embong, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to investigate the association between board characteristics and firm value taking into consideration the role of investors’ confidence. The subject of corporate governance is still of interest to researchers and practitioners due to its importance and the complexities surrounding it. This is because there are many elements that may interplay with corporate governance in influencing the value of firms. Despite abundance of research on the effect of board characteristics on firm’s value, the empirical evidences are still inconclusive. One of the consequences of having good governance as evidenced by many empirical research is the higher firm value. The agency theory explains this relationship such that good governance reduces agency cost, increasing investors’ confidence on the firm, hence its value. This explanation indicates that the influence of good governance on the firm’s value could be due to its effect on investors’ confidence. This study extends the understanding on the relationship between corporate governance and firm value by investigating the role of investors’ confidence on this relationship. Companies listed on Main Board of Bursa Malaysia are selected as sample using proportionate stratified random sampling method. The results demonstrate that CEO duality and board independence significantly related to firm value consistent with prior studies. The analysis on the role of investors’ confidence in the relationship between board characteristics and firm value indicates that investors’ confidence plays significant role in the relationship between CEO duality and firm value. The results provide input to firms on factors that contribute to firm value and to relevant authority on the important aspect of corporate governance.